Duck Dodgers. Season 1 [videorecording (DVD)] Dark side of the duck (Warner Home Video, 2013)
Launch into a series of zany adventures with everyone's favorite fighter of Martian tyranny. Duck Dodgers is always ready to swoop in and save the day, the planet, and the galaxy-with a little luck and a lot of help, that is. He may be an intellectual featherweight, but his duckbilled laser gun counts as heavy artillery. So sit back, buckle up, and enjoy a hilarious flight of fantasy filled with light-years of intergalactic intrigue and futuristic fun.